A sound of thunder - Hyams, Peter; Diamant, Moshe; Donnelly, Thomas Dean; Burns, Edward; McCormack, Catherine; Kingsley, Ben; Rooper, Jemma; David Oyelowo; Walz, Esther; Walz, Esther; Louthan, Guy; Smith, Nick Glennie; et al.
A group of hunters go back in time to hunt dinosaurs. In doing so, they inadvertantly touch off a new and divergent course of evolution that threatens human exi